Eksistensi bangunan gaya kolonial Belanda di kawasan Kayutangan, Kota Malang pada tahun 1900-2021 - Khamaliyah Nur Erine; Sakafitri Rimasari; Ari Sapto (Universitas Negeri Malang, 2022)
The history of the city of Malang has a long journey until the presence of the city of Malang is rapidly as it is today. Judging from its history, in 1914 the Kayutangan area to the Malang city square was used as the center of Malang city at that time. This is because the geographical location of Kayutangan is very strategic for trade and service routes and is used as a connecting route between Malang and Surabaya. The pattern of settlements is formed around the square with the pattern following the grouping of a plural society. Most of the colonial buildings in Malang adhere to Dutch architecture. Colonial buildings built before the 1920s have an